The influence of tourist satisfaction on revisit intention: the moderating role of health consciousness - Suliyanto, Suliyanto; Rahab, Rahab; Arini, Destia Vindha (Intelektual Pustaka Media Utama, 2024)
Cleanliness, health, safety, and environment sustainability (CHSE) certification is an indicator of a COVID-19-safe tourist destination. Baturraden tourist destination has received a CHSE level certificate very good but the effect is not yet known on tourist satisfaction and intention to visit again. This study aimed to analyze the effect of the element CHSE on revisit intention through tourist satisfaction and health consciousness as a moderating variable. This research is survey research by collecting data from 149 respondents who had visited the Baturraden tourist destination. Five Likert scale is used to measure research construct. To test the causal relationship between constructs, structural equational modelling (SEM) with SmartPLS is used. The findings of this research are cleanliness, environmental sustainability, health, and safety have a positive effect on tourist satisfaction, and tourist satisfaction has a positive effect on revisit intention, but health consciousness and the moderating effect of health consciousness have no effect on revisit intention.